2017
DOI: 10.1038/ncomms14258
|View full text |Cite
|
Sign up to set email alerts
|

C-edge loops of arrestin function as a membrane anchor

Abstract: G-protein-coupled receptors are membrane proteins that are regulated by a small family of arrestin proteins. During formation of the arrestin–receptor complex, arrestin first interacts with the phosphorylated receptor C terminus in a pre-complex, which activates arrestin for tight receptor binding. Currently, little is known about the structure of the pre-complex and its transition to a high-affinity complex. Here we present molecular dynamics simulations and site-directed fluorescence experiments on arrestin-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 52 publications
11
91
0
Order By: Relevance
“…The Arr2-NTSR1 complex is formed by asymmetric assembly of the two components with the horizontal axis of Arr2 intersecting the inner surface of the cell membrane at about 20°, resulting in the interaction of the hydrophobic C-edge loops (L191 and M192, and L334 through L338) of the arrestin with the cell membrane (Fig 2a&b). This is consistent with the crystal structure of visual arrestin-rhodopsin complex, which for the first time displayed the asymmetric arrestin-GPCR assembly and confirmed the function of the hydrophobic C-edge loops of arrestin as a membrane anchor that stabilizes the binding of arrestin to membrane-embedded receptor, which was later confirmed experimentally 7,26,27 . The interaction of the hydrophobic C-edge loops of the Arr2 with cell membrane layer suggests that the lipid binding capability is a general property of the arrestin family members.…”
Section: The Overall Structure Of the Arr2-ntsr1 Complexsupporting
confidence: 87%
“…The Arr2-NTSR1 complex is formed by asymmetric assembly of the two components with the horizontal axis of Arr2 intersecting the inner surface of the cell membrane at about 20°, resulting in the interaction of the hydrophobic C-edge loops (L191 and M192, and L334 through L338) of the arrestin with the cell membrane (Fig 2a&b). This is consistent with the crystal structure of visual arrestin-rhodopsin complex, which for the first time displayed the asymmetric arrestin-GPCR assembly and confirmed the function of the hydrophobic C-edge loops of arrestin as a membrane anchor that stabilizes the binding of arrestin to membrane-embedded receptor, which was later confirmed experimentally 7,26,27 . The interaction of the hydrophobic C-edge loops of the Arr2 with cell membrane layer suggests that the lipid binding capability is a general property of the arrestin family members.…”
Section: The Overall Structure Of the Arr2-ntsr1 Complexsupporting
confidence: 87%
“…Importantly, we observed electron density for the membrane-touching loop of arrestin (C-edge loop) from residue 340 through 342 (Figure S1C). Molecular dynamics simulation indicated that C-edge loops of arrestin function as membrane anchors, whose engagement with membrane is required for GPCR binding by arrestins (Lally et al, 2017). We also observed electron density for poly N-acetyl-D-glucosamine at the N15 glycosylation site of each rhodopsin molecule (Figure S1D), and most of the rhodopsin C-terminal tail (residues 330–343) including two phosphate groups at T336 and S338 (Figures 1, 2 and S1E–F).…”
Section: Resultsmentioning
confidence: 99%
“…We verified biochemically that PIP2 binding to this determinant is sufficient to partition β-arrestin out of the solution phase (Extended Data Figure 6e, f). This phosphoinositide-binding determinant is specific to β-arrestins but a lipid-anchoring region in the C-domain was recently identified visual arrestin 33 . Mutating the homologous residues in β-arrestin did not prevent accumulation at the plasma membrane or in CCSs (Extended Data Table 1; Extended Data Figure 6g, h).…”
Section: Capture After Gpcr Dissociationmentioning
confidence: 99%